2009
DOI: 10.1016/s1474-4422(09)70107-3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced neuroimaging of migraine

Abstract: Advanced neuroimaging has led to an evolution in knowledge about migraine pathophysiology. Migraine has transformed from a vascular, to neurovascular, and most recently, to a central nervous system disorder. Functional imaging has confirmed the importance of cortical spreading depression (CSD) as the pathophysiologic mechanism of migraine aura in humans, while novel animal studies are unraveling the mechanistic underpinnings of CSD. Altered cerebral blood flow and neurotransmitter systems have been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
155
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 75 publications
10
155
1
1
Order By: Relevance
“…These studies have shown a widespread subcortical and cortical brain network involved in pain processing in migraine subjects. However, one of the main challenges in the interpretation of these results is to differentiate findings consistent with a general pain response from those that might be specific to migraine [11,12]. Nevertheless, a noxious stimulation paradigm, using a contact thermode [26], has been extensively used in different BOLD-fMRI studies to elucidate mechanisms underlying pain processing in migraine subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown a widespread subcortical and cortical brain network involved in pain processing in migraine subjects. However, one of the main challenges in the interpretation of these results is to differentiate findings consistent with a general pain response from those that might be specific to migraine [11,12]. Nevertheless, a noxious stimulation paradigm, using a contact thermode [26], has been extensively used in different BOLD-fMRI studies to elucidate mechanisms underlying pain processing in migraine subjects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in event-related experiments BOLDfMRI response is modeled as the linear summation of the hemodynamic response to discrete events [10]. It is well known that migraine episodes are typically unpredictable while BOLD-fMRI studies require considerable planning and this justify the scarcity of fMRI data during spontaneous attacks of migraine [11]. In consequence, BOLDfMRI research field has been dominated by event-related experiments, specifically triggered migraine attack or experimental acute-pain studies, during interictal period.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Previous theories have focused on vascular causes and extracranial vasodilation being responsible in causing the migraine attacks. 25,26 Now migraine can no longer be considered a vascular or a neurovascular disorder, but instead should be thought of as a disease mediated by the central nervous system. 26 Current theories on migraine argue that the trigeminal nerve that innervates the meninges affects pain-sensitive vascular structures in the dura mater, base of skull, and scalp that are involved in the migraine attack.…”
Section: Discussionmentioning
confidence: 99%
“…This finding offers an important clue for the mechanism of migraine and may indicate a potential therapeutic option; namely, the possibility that sodium depletion is involved with migraine onset and persistence. The anatomy of migraine is now visible in scanners [10][11][12][13][14]. Depolarized regions, zones of cortical depression (CD), are unable to generate energy for action potential [16].…”
Section: Introductionmentioning
confidence: 99%